PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL KARYAWAN PADA PT CARMIN MAJU BERSAMA INDONESIA - Erninawati, Erninawati; Mardika, Nanda Harry (LPPM Universitas Putera Batam, 2021)
The research sample consisted of 118 employees at PT Carmin Maju Bersama Indonesia. Data were collected by distributing questionnaires directly and analyzed using SPSS 23. The results of the F test are known to be 177.922> F table 3.07 with a significant 0.000 <0.05, it can be concluded that the variables of organizational culture (X2) and job satisfaction (X2) simultaneously on employee organizational commitment (Y). The results of the t test for organizational culture and job satisfaction (X1) 5.491> t table 1.98081 with a significant 0.000 <0.05 so that the organizational culture variable (X1) has a significant effect on employee organizational commitment (Y). The results of the t test job satisfaction (X2) 8,010> t table 1,98081 with a significant 0,000 <0,005 so that job satisfaction (X2) has a significant effect on employee organizational commitment (Y). The results of the calculation of the coefficient of determination (R2) obtained 0.756 or 75.6% of the employee organizational commitment variable (Y) can be explained by the variables of organizational culture and job satisfaction and the remaining 24.4% is another variable that has an influence on the bound which the researcher does not take in the study this.